The Impact of Ligand Removal on the Optoelectronic Properties of Inorganic and Hybrid Lead Halide Perovskite Nanocrystal Films - Papagiorgis, Paris; Sergides, Marios; Manoli, Andreas; Athanasiou, Modestos; Bernasconi, Caterina; Galatopoulos, Fedros; Ioakeimidis, Apostolos; Nicolaides, Constantinos; Leontidis, Epameinondas; Trypiniotis, Theodossis; Choulis, Stelios A.; Bodnarchuk, Maryna I.; et al. (My University, 2024)
Ligand exchange performed during or after the colloidal synthesis of nanocrystals (NCs) provides an efficient way to produce conductive NC solids for optoelectronics. Herein, a post-synthetic ligand washing process is developed and applied to two different combinations of ligands and perovskite NCs, namely robust green CsPbBr3 NCs capped by didodecyldimethylammonium bromide and near-infrared FAPbI3 NCs decorated by weakly bound oleic acid ligands. The impact of such processes on the morphological and optoelectronic NC properties is examined while exploring parameters such as the reaction time and the influence of oxygen and humidity. For the FAPbI3 NCs, ligand washing results in extended NC aggregation and substantial photoluminescence loss, with the treatment becoming more aggressive for air-exposed films. For the CsPbBr3 NCs, the process is insensitive to the environmental conditions and results in partial ligand shell loss and NC close packing rather than bulk-like aggregation while affecting less the optical properties. Upon ligand removal, the photoconductance increases by up to ≈90% and ≈60% for FAPbI3 NCs and CsPbBr3 NCs, respectively. THz spectroscopy produces qualitatively similar trends of the conductivity with ligand removal time, with THz mobility values as high as 30 and 6 V−1s−1cm2 for glove box prepared FAPbI3 and CsPbBr3 NCs, respectively.
Keywords: lead halide perovskites; ligands; photoconductivity; nanocrystals; photoluminescence; THz spectroscopy